Respuesta :

Answer:

D

Step-by-step explanation:

using the definition of n[tex]P_{r}[/tex] = [tex]\frac{n!}{(n-r)!}[/tex]

where n! = n(n- 1)(n - 2)......× 3 × 2 × 1

here n = 7 and r = 4, hence

7[tex]P_{4}[/tex]

= [tex]\frac{7!}{3!}[/tex]

= [tex]\frac{7(6)(5)(4)(3)(2)(1)}{3(2)(1)}[/tex] ← cancel 3 × 2 × 1 leaving

7[tex]P_{4}[/tex] = 7 × 6 × 5 × 4 = 840 → D


The expression is an illustration of permutation.

The result of  [tex]\mathbf{^7P_4}[/tex] is (d) 840

The expression is given as:

[tex]\mathbf{^7P_4}[/tex]

The formula of permutation is:

[tex]\mathbf{^nP_r = \frac{n!}{(n-r)!}}[/tex]

So, we have:

[tex]\mathbf{^7P_4 = \frac{7!}{(7-4)!}}[/tex]

[tex]\mathbf{^7P_4 = \frac{7!}{3!}}[/tex]

Expand

[tex]\mathbf{^7P_4 = \frac{7 \times 6 \times 5 \times 4 \times 3!}{3!}}[/tex]

[tex]\mathbf{^7P_4 = 7 \times 6 \times 5 \times 4 }[/tex]

[tex]\mathbf{^7P_4 = 840}[/tex]

Hence, the result of  [tex]\mathbf{^7P_4}[/tex] is (d) 840

Read more about permutation at:

https://brainly.com/question/1216161

ACCESS MORE